Effect of Regular Exercise on Cognitive Frailty in the Elderly: A Systematic Review. - Ji, Wenting; Sun, Liwei; Geng, Qian; Zheng, Guohua (Experimental Aging Research)
Objectives: As one of the common senile syndromes characterized by the co-existence of physical frailty and cognitive impairment without dementia, the occurrence of cognitive frailty (CF) increases the risk of adverse health outcomes in older adults. However, its reversibility has attracted the interest of researchers in the search for effective interventions. A growing number of studies have been conducted to investigate the effect of regular physical exercise intervention on cognitive frailty in older adults with CF, but findings remain inconclusive. This study aimed to synthesize the pooled effect of current regular exercise intervention in community-dwelling older adults with cognitive frailty. Methods: Nine electronic databases (Cochrane Library, PubMed, EBSCOHost, Web of Science, Scopus, CNKI, Wanfang Database, VIP and SinoMed) were searched from their inception to 15 May, 2024. The Cochrane risk-of-bias tool (ROB 2) for RCTs was applied to assess the methodological quality. The mean difference or standardized mean difference with 95% CIs was calculated by using Stata 18.0. Results: Seventeen eligible studies involving a total of 2239 participants were included. The pooled results showed that older adults with CF in the intervention group had significant improvement in global cognitive function performance (MMSE scores: MD = 1.93 95% CI: 1.02 to 2.85, p <.0001, and MoCA scores: MD = 3.24, 95% CI: 1.57 to 4.91, p <.0001), executive function (time of TMT-B test: MD = -20.73, 95% CI: −33.96 to −7.50, p =.002), physical frailty state (Fried frailty phenotype scores: MD = -1.48, 95% CI: -2.37 to −0.58, p =.001, and EFS scores: MD = −0.81 points, 95% CI: -1.13 to −0.49, p <.0001), grip strength (SMD = 0.92, 95% CI: 0.15 to 1.07, p =.02), gait and balance (time of TUG: MD = −2.62, 95% CI: −4.12 to −1.11, p =.001), balance (BBS scores: MD = 8.56, 95% CI:- 3.37 to 13.75, p =.001) and quality of life (SMD = 0.75, 95% CI: 0.30 to 1.21, p =.001). Conclusions: More than eight weeks of regular exercise interventions may improve global cognitive function and physical frailty status, but the effect on specific domains of cognitive or physical function needs further study to confirm.